Estudo da modificação superficial por processos mecânico e à plasma sequencial no aço inoxidável austenítico ABNT 316L - Marcela Rabelo Menezes (2014)
Austenitic stainless steels are widely used due to the different properties they have as high conformability, good corrosion resistance. However, these steels do not exhibit good wear resistance and high hardness. In order to improve the wear resistance and increased surface hardness of these steels, treatments were made on the surface of them. Six systems were studied: the austenitic stainless steel AISI 316L as received, the sequential system at 400 oC (AISI 316L stainless steel as received cemented by plasma for two hours followed by plasma nitriding for two hours at a temperatura of 400 oC), the sequential system at 475 oC (AISI 316L stainless steel as received cemented by plasma for 2 hours followed by plasma nitriding for two hours at 475 oC), the system wherein a mechanical pretreatment on stainless steel (called shot peening) was performed, the system shot peening over sequential treatment at 400 oC (AISI 316L stainless steel as received withpre-shot peening cemented by plasma for two hours followed by plasma nitriding for two hours at 400 oC) and shot peening system and sequential treatment to 475 oC (AISI 316L stainless steel with pre-shot peening, cemented by plasma process for two hours followed by plasma nitriding for two hours at 475 oC). The systems were characterized by scanning electron microscopy (SEM), X-ray spectroscopy by dispersive energy (EDS), X-ray diffraction (XRD), glow discharge optical emission spectroscopy (GDOES) and profilometry. Dry wear pin on disc configuration, instrumented indentation testing and also tests of anodic potentiodynamic polarization tests were performed. Systems with shot peening before the sequential plasma process of carburizing andnitriding showed better wear resistance than those in which pre treatment were not performed. Comparing just systems at different temperaturas showed that the systems were performed at 475 oC performed better than those that were performed at 400 oC showing the strong influence of temperatura on the results. All systems that had some type of treatment had better results as regards wear resistance compared to steel asreceived. The instrumented indentation testing showed that the shot peening caused a higher hardness near the surface of the treated systems at both temperatures 400 and 475 oC. Close to the surface, the hardness was higher and also had a greater depth of hardening .The anodic potentiodynamic polarization tests in 0.5 M sulfuric acid indicated no modifications on the corrosion resistance of the systems compared to untreated AISI 316L stainless steel, in which the termochemical plasma treatment was carried out at a temperature of 400 oC with or without the shot peening. In systems where the plasmaprocesses were performed at 475 oC, there was the formation of chromium nitrides impoverishing the austenitic matrix in relation to the element chromium, which caused less corrosion resistance of these systems. Therefore, after the surface treatment 400 °C, austenitic stainless steel AISI 316L can be used in conditions requiring wear resistance, greater hardness and corrosion resistance simultaneously. Systems in which the plasma treatment was conducted at 475 oC showed high wear resistance and a higher hardness,